Improving Digital Literacy of Village Communities in Indonesia through Information Technology-Based Community Service Programs - Budiarto, Balla Wahyu; Karyadi, Sugeng; Wasiran, Wasiran; Pratiwi, Ratih; Irwan, Dedy (Pascasarjana Universitas Mataram, 2024)
This Community Service Program (PKM) aims to improve the digital Literacy of rural communities in Indonesia through information technology-based Training. This activity was conducted online and involved 50 participants with a varied basic understanding of digital technology. Interactive training methods using the Zoom application and mentoring via WhatsApp are carried out to ensure participants can understand and practice the training material, especially in social media and e-commerce. The Training results showed a significant improvement in the participants' abilities. Before the Training, only 20% of participants could use social media, and 15% could take advantage of e-commerce. After the Training, this figure increased to 85% and 70%, respectively. Although there are challenges in the form of limited internet access in some regions, the provision of materials that can be accessed offline helps participants in the learning process. This program increases digital Literacy and contributes to improving the local economy through digital marketing of village products. With positive results, this program can be replicated in other regions to empower the community through information technology. This study shows that the right digital training approach can significantly impact Literacy and economic empowerment in rural communities.